Preferência de Atta sexdens rubropilosa Forel, 1908 e Atta laevigata F. Smith, 1858 (Hymenoptera: Formicidae) por diferentes espécies e híbridos de Eucalyptus spp., de localidades distintas do estado de Mato Grosso - Santos, Joilson Onofre Pereira dos (2012)
This work aimed to evaluate the preference of Atta sexdens rubropilosa (Forel, 1908) and Atta laevigata (F. Smith, 1858) by different species, hybrids and clones of Eucalyptus, from different regions of the state of Mato Grosso, in conditions of field. Therefore, it was collected leaf samples from 21 treatments planted in December/2008 in states of Itiquira, Santa Rita do Trivelato and Sinop. The attractiveness tests were made in October/2010 in the field, in a nest near to the Federal University of Mato Grosso – UFMT, evaluating the preference of Atta sexdens rubropilosa in October/2011 and other nests near to the region of Chapada dos Guimarães, assessing preference for Atta sexdens rubropiosa and Atta laevigata. For attractiveness testing, aluminum plates numbered were used, and each treatment of eucalyptus was considered a treatment. In each aluminum plate it was placed 25 follicles per treatment and the plates were arranged along the carrier of the active ant, with four replications for each treatment. The design was completely random and activity was assessed by determining the amount of leaf discs carried in each treatment, and the data analyzed by the Scott Knott test at 5% probability. It was concluded that age influences the preference of foraging by Atta sexdens rubropilsa. The edaphoclimatic factors influence the preference for charging leaf by leaf cutter Atta laevigata and Atta sexdens rubropilsa. Atta laevigata and Atta sexdens rubropilsa have a preference for charging the hybrid urograndis leaf discs. Atta sexdens rubropilsa and Atta sexdens rubropilsa preferably have a lower load per leaf discs of the species Eucalyptus camaldulensis and Corymbia citriodora. Atta sexdens rubropilsa and Atta laevigata have preferably lower load per leaf discs from seminal species compared with the discs from clones.